2011
DOI: 10.1038/hdy.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

A steep cline in ladybird melanism has decayed over 25 years: a genetic response to climate change?

Abstract: A cline in the frequency of melanic morphs of the two-spot ladybird, Adalia bipunctata, was first surveyed in 1980 along a transect extending inland from the coast in the Netherlands. At that time, the frequency of melanics increased over some 40 km from 10% near the coast to nearly 60% inland. Additional surveys made in 1991 and 1995 demonstrated some progressive change in cline shape. New samples from 1998 and 2004 confirm these dynamics, and show that over a period of about 50 generations for the beetle, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 23 publications
(23 reference statements)
1
36
0
Order By: Relevance
“…They lead to local differences in the proportions of the different morphs (Komai & Hosino, 1951;Bengtson & Hagen, 1975) and can change relatively fast when the climate changes (Brakefield & Lees, 1987;de Jong & Brakefield, 1998;Majerus & Zakharov, 2000;Brakefield & de Jong, 2011). It is unlikely that thermoregulation has affected the percentages of the different morphs in the Sturovo population of H. variegata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They lead to local differences in the proportions of the different morphs (Komai & Hosino, 1951;Bengtson & Hagen, 1975) and can change relatively fast when the climate changes (Brakefield & Lees, 1987;de Jong & Brakefield, 1998;Majerus & Zakharov, 2000;Brakefield & de Jong, 2011). It is unlikely that thermoregulation has affected the percentages of the different morphs in the Sturovo population of H. variegata.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of morphs in populations of A. bipunctata in xeric Central Europe has remained stable for 33 years (Honek et al, 2005) while in populations in areas with a humid oceanic climate it has changed. It is suggested that these changes are determined by the level of industrial air pollution (Creed, 1971;Zakharov, 2003) and changes in climate (de Jong & Brakefield, 1998;Brakefield & de Jong, 2011). Directional long-term changes also occur in local populations of H. axyridis (Komai & Chino, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of temperature on f. succinea is intriguing; individual H. axyridis f. succinea (non‐melanic) eclosing from pupae late in the year have larger spots than those eclosing in spring and early summer (Michie et al ., ). Recent research has indicated that the phenotypic plasticity displayed by H. axyridis enables local adaptation at temporal and spatial scales (Michie et al ., ), whereby melanism, which may be important in thermoregulation (Brakefield & de Jong, ), is considered costly in summer and beneficial in winter (Michie et al ., ). Michie et al .…”
Section: Factors Affecting the Population Demography Of Harmonia Axyrmentioning
confidence: 99%
“…In particular the multicolored Asian lady beetle Harmonia axyridis is an attractive organism for research because of its highly variable red and black coloration and multiple color forms. In addition there is a strong genetic component to the pigmentation of H. axyridis which makes it a valuable organism for understanding how genes and the environment contribute to coloration (Wittkopp and Beldade, 2009; Brakefield and de Jong, 2011). H. axyridis is endemic to northeast Asia but has been well established throughout much of the U.S. following their introduction in the southern U.S. in the 1980s in an attempt to control aphid populations (Roy and Wajnberg, 2008).…”
Section: Introductionmentioning
confidence: 99%